Environmental Signals Controlling Production of Hemagglutinin/Protease in Vibrio cholerae - Benitez, Jorge A. (American Society for Microbiology, 2001)
Vibrio cholerae hemagglutinin/protease (Hap) was induced upon nutrient limitation and strongly repressed by glucose. Hap was not produced in a mutant defective in the cyclic AMP (cAMP) receptor protein, suggesting that intracellular cAMP levels mediate Hap expression. No difference was found in Hap production between an rpoS deletion mutant and its isogenic wild-type precursor, indicating that the alternate ς(s) factor is not essential for Hap expression. Based on these and previous results, we discuss the role of Hap in the pathogenesis of cholera.